2019
DOI: 10.1111/nin.12292
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the ‘self’ in self‐management of chronic illness: Lessons from relational autonomy

Abstract: Self‐management is often presented as a panacea for chronic disease care. It plays an important role at the policy level and increasingly guides the delivery of health care services. Self‐management approaches to care are founded on traditional individualistic views of autonomy in which the patient is understood as being independent, rational, self‐interested, and self‐governing. This conceptualization of autonomy has been challenged, particularly by feminist scholars. In this paper I review predominant critiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…Relational autonomy is a perspective that frames individuals as socially embedded agents who develop a sense of self through the context of social relationships; it proposes that people are inherently interdependent and interconnected. These social relationships are shaped by the intersection of SDH (19). It is a notion of autonomy that is sensitive to issues of social justice and is socially grounded.…”
Section: Ethical Justification For a Harm Reduction Approachmentioning
confidence: 99%
“…Relational autonomy is a perspective that frames individuals as socially embedded agents who develop a sense of self through the context of social relationships; it proposes that people are inherently interdependent and interconnected. These social relationships are shaped by the intersection of SDH (19). It is a notion of autonomy that is sensitive to issues of social justice and is socially grounded.…”
Section: Ethical Justification For a Harm Reduction Approachmentioning
confidence: 99%
“…Several studies have found that the social context of a person's life determines not only the risk of exposure and the degree of susceptibility but also the course and outcome of a disease depending on the capability to cope with the disease ( 8 , 17 , 18 ). However self-management of CHC is too often discussed from a purely individualistic perspective, ignoring the social and cultural context in which this process happens ( 19 , 20 ). “Central to these critiques is a hyper-individualistic conception of patients as autonomous self-regulating subjects making self-serving decisions” ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However self-management of CHC is too often discussed from a purely individualistic perspective, ignoring the social and cultural context in which this process happens ( 19 , 20 ). “Central to these critiques is a hyper-individualistic conception of patients as autonomous self-regulating subjects making self-serving decisions” ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that the social context of a person's life determines not only the risk of exposure and the degree of susceptibility but also the course and outcome of a disease depending on the capability to cope with the disease [7]. However self-management of CHC is too often discussed from a purely individualistic perspective, ignoring the social and cultural context in which this process happens [14,15]. "Central to these critiques is a hyper-individualistic conception of patients as autonomous self-regulating subjects making self-serving decisions" [14].…”
Section: Introductionmentioning
confidence: 99%
“…However self-management of CHC is too often discussed from a purely individualistic perspective, ignoring the social and cultural context in which this process happens [14,15]. "Central to these critiques is a hyper-individualistic conception of patients as autonomous self-regulating subjects making self-serving decisions" [14].…”
Section: Introductionmentioning
confidence: 99%